COVID-19: Potential Repurposing Drugs - Leowattana, Wattana (Infectious Disorders - Drug Targets, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is one of the most infectious diseases which has been caused by coronavirus in 2019 (COVID-19). It has widely spread worldwide and infected more than 28 million people in 215 countries, and more than 920,000 have now died from COVID-19. To date, no effective antiviral drugs or specific vaccines have been discovered yet. Considering this situation, the potential therapeutic antiviral drug targets for the COVID-19 are being repurposed to speed up the discovery of effective treatment. The most potential drug targets that are continuously being recommended include Favipiravir, Chloroquine, Hydroxychloroquine, and Remdesivir. Moreover, the antiviral target proteins and anti-host target proteins are being reported continuously. This review has summarized the current research studies on potential therapeutic drug targets that are being tested against the SARS-CoV-2. It will provide information related to potential repurposing drugs for overcoming COVID-19.
Keywords: repurposing drugs